JANIE CRAWFORD'S ALIENATION IN ZORA NEALE HURSTON'S THEIR EYES WERE WATCHING GOD - Pujimahanani, Cahyaningsih; Sayang, Niki Saka (Faculty of Letters, Dr. Soetomo University, 2016)
Zora Neale Hurston's Their Eyes Were Watching God is a novel that reflects African-American social life in the early 20th century. This thesis examines the proofs of Janie Crawford alienation in every aspect of her life. In order to analyze the problem, the thesis uses a theory of alienation stated and applies qualitative method. Firstly, the thesis begins to read the novel and then collects the data. Then, this thesis carry on the process of analyzing the data collecting with the theory and making a conclusion at last. The findings of this thesis exhibits Janie Crawford's powerlessness and self-estrangement that can be seen through every events of her life with her familiarpeople. Keywords: Alienation, Powerlessness, Self-estrangement